Experimental study on short-circuit current characteristics of a photovoltaic system with low voltage ride through capability under a symmetrical fault - Shuai Yuan; Bao-Feng Yang; Jian-Ying Zhang (Energy Reports, 2022)
Large number of photovoltaic (PV) power plants connected to a power grid can bring significant impacts to fault currents and the operation of protection systems. In this paper, short-circuit current characteristics of a PV system with low voltage ride through (LVRT) capability under a symmetrical fault is studied. PV system short-circuit experiments with different voltage dips at high and low output power levels are designed and conducted. The experiment results provide useful and valuable references for researches of PV system short-circuit current characteristics, modeling and PV system short-circuit current contribution to a power grid. Then, based on the experiment results, steady-state values, peak values and steady state short-circuit currents harmonic characteristics at different conditions are obtained and analyzed. It is found that, the DC component amplitude of a PV system short-circuit current is almost negligible compared with that of the power frequency component, which is different from conventional synchronous generator short-circuit current. Meanwhile, based on the LVRT control strategy and experimental results, the expression of steady-state short-circuit current RMS value is derived and verified, which provides an important basis for short-circuit current calculation of power system with large scale of PV plants.